Clinical outcome of operative treatment in 18 cases of giant cell tumors of bones - Pandey, Suresh (Journal of Chitwan Medical College, 2020)
Background: Giant Cell Tumor of the bone (GCTB) has got variable outcome after the different methods of surgical treatment depending upon the site and grade of lesion and extent of tumor removal. This retrospective prospective analysis of operatively treated cases of GCTB of different sites aimed to highlight the clinical outcome. Methods: This was a prospective observational study of 18 cases of GCTB; proximal tibia (n=6), distal femur (n=5), distal radius (n=4), proximal femur (n=1), proximal fibula (n=1) and anterior arc of first rib (n=1) treated with different operative management with mean follow up of 53.61 months. Functional outcome with Musculoskeletal Tumor Society Score (MSTS), recurrence and complications were analyzed with at least 24 months of follow up. Results: There were 10 females and 8 males with average age at presentation 27.3 years (range 15-38). Average duration of symptom was 4.72 months. 2 were cases of recurrence previously operated and 16 were de novo cases. Mean MSTS was 84.27% with good to excellent result in 88%. There were no non-union, graft failure, metastasis, prosthetic failure or wound infection till at least 24 months of follow up in any of the cases. Conclusions: Extended curettage or reconstruction with auto graft in grade I and II tumor or endoprosthesis in higher grade or recurrence of GCTB can give good to excellent functional result in majority of the cases.